Analisis Karakter Gemar Membaca Peserta Didik Sekolah Dasar - Fatmasari, Era; Alfiana, Rizki; Silvia, Ninda; Sinambella, Parasian (Journal of Basic Education Research, 2022)
Research Objectives: This study aimed to determine the character of students' love of reading. Research Methods: This research is qualitative research. The method used is phenomenology which focuses on a person's experiences. Main Findings: The results of this study show that there have been various efforts made by the school to move the character of students' love of reading. Novelty of this Research: The novelty of this study is to find how the character likes to read students in class V of SD Negeri 076/I Sungai Buluh.